Impact of Acute Myocardial Ischemia Duration on Reperfusion Outcomes in STEMI Patients - Salo, Sergii V.; Shpak, Serhii S.; Shumakov, Valentyn O. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To analyze the influence of the duration of acute myocardial ischemia, specifically in ST-elevation myocardial infarction (STEMI) electrocardiographic patterns, on the outcomes of reperfusion interventions. We focused on the assessment of immediate angiographic data in the catheterization laboratory after stenting and investigated whether the frequency of the no-reflow phenomenon is dependent on the time since the onset of anginal pain. Our hypothesis of inferior immediate treatment outcomes is based on the pathophysiological course of ischemic-reperfusion injury in patients with late myocardial infarction. Primarily, this is due to the development of myocardial edema, leading to extravascular compression of the vessel, thereby influencing Thrombolysis in Myocardial Infarction grade 0 blood flow. Materials and methods. We conducted an analysis of 107 angiograms of STEMI patients, who underwent percutaneous coronary intervention at the Amosov National Institute of Cardiovascular Surgery between 2021 and 2023. The patients were categorized into four groups based on the duration of acute myocardial ischemia. The first group included patients with ischemia duration up to two hours, aligning with the golden window for revascularization recommended by the European guidelines. The second, third, and fourth groups consisted of patients with ischemia durations of 3-12 hours, 12-24 hours, and over 48 hours, respectively. Results. Of 104 patients, complete restoration of coronary circulation was achieved in 88 cases, while, unfortunately, 16 patients had TIMI 0/1 blood flow. Such a probability of complication is 15.3% in the studied cohort. According to the clinical profile, the patients were divided into those who had no-reflow (main group) and patients with complete restoration of blood flow (control group). In the group of unrestored blood flow, cardiogenic shock occurred more often, and the infarct-dependent artery was more often occluded than suboccluded. The technique of percutaneous intervention was similar in both groups. Conclusion. The frequency of the no-reflow phenomenon increases with the duration of acute myocardial ischemia. Patients presenting later than 48 hours since the onset of ischemia are more prone to no-reflow (62.5% vs 37.5% if less than 48 hours). Cardiogenic shock is associated with a higher likelihood of the no-reflow phenomenon. The most significant reason for the delay in delivering a STEMI patient to catheterization laboratory anamnestically is the patient’s untimely medical care seeking. In our opinion, this delay can be avoided by increasing awareness about the initial signs of myocardial infarction and the necessity of seeking immediate medical care.